2015
DOI: 10.3102/0162373715576076
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Math Acceleration and Equitable Access to Eighth-Grade Algebra

Abstract: Taking algebra by eighth grade is considered an important milestone on the pathway to college readiness. We highlight a collaboration to investigate one district's effort to increase middle school algebra course-taking. In 2010, the Wake County Public Schools began assigning middle school students to accelerated math and eighth-grade algebra based on a defined prior achievement metric. This policy reduced the relationship between course assignment and student characteristics such as income and race/ethnicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Edmunds et al [2010] found that being assigned to an ECHS had strong, positive impacts on ninth grade student outcomes. Students given access to an ECHS were significantly more likely to enroll in and complete Algebra I, considered a gateway course for college-preparatory mathematics [Dougherty et al, 2015], as well as have lower rates of school absence and suspension. In addition, those offered the ECHS opportunity were five percentage points more likely to be "on-track" for college at the completion of ninth grade, meaning that they were on-track to complete the Future-Ready Core Graduation Requirements specified by the state of North Carolina.…”
Section: Early College High Schoolsmentioning
confidence: 99%
“…Edmunds et al [2010] found that being assigned to an ECHS had strong, positive impacts on ninth grade student outcomes. Students given access to an ECHS were significantly more likely to enroll in and complete Algebra I, considered a gateway course for college-preparatory mathematics [Dougherty et al, 2015], as well as have lower rates of school absence and suspension. In addition, those offered the ECHS opportunity were five percentage points more likely to be "on-track" for college at the completion of ninth grade, meaning that they were on-track to complete the Future-Ready Core Graduation Requirements specified by the state of North Carolina.…”
Section: Early College High Schoolsmentioning
confidence: 99%
“…The bias being that with only high-achieving students provided the opportunity of taking Algebra I in Grade 8, those middle-of-theroad students, who may be successful in Algebra I, are not given the opportunity to go on to advanced coursework later on in high school (Coltfelter, Ladd & Vigdore, 2012;Rickles, 2013). Other factors, such as teacher recommendations often exclude students who may benefit from an advanced pathway as well (Dougherty, Goodman, Hill, Litke & Page, 2015).…”
Section: Student Achievement Selection Bias and Trackingmentioning
confidence: 99%
“…In this sense, Algebra I can be viewed as a gatekeeper course (Dougherty, Goodman, Hill, Litke & Page, 2015;Rickles, 2013). Early access to Algebra I, or the lack thereof, determines subsequent high school mathematics courses (Smith, 1996).…”
Section: Student Achievement Selection Bias and Trackingmentioning
confidence: 99%
See 2 more Smart Citations